Bear hugs : romantically ridiculous animal rhymes - Wilson, Karma; Watts, Suzanne (New York : Margaret K. McElderry Books, 2005)
A collection of eighteen short poems celebrating love and friendship between animals, from cats and sheep to giraffes and crocodiles.
Accelerated Reader AR
Keywords: Animals -- Juvenile poetry; Children's poetry, American; Animals -- Poetry; Love -- Poetry; American poetry